Inovasi Mie Kopi sebagai Upaya Pengembangan Potensi Kopi Lokal di Desa Sagalaherang Melalui Program Kerja Kuliah Kerja Nyata (KKN) - Ghina Nabilah Fauziyyah; Hana Astria Nur; Brian Febriansyah; Fahmi Hikmahtul Ikhsan; Septi Jihan Alifa; Rofi Fitriyah; Dandi Mahfudin; Eka Satrio Touladan (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service program was conducted in Sagalaherang Village, Ciamis Regency, with the objective of developing local coffee potential through culinary innovation in the form of coffee noodles. The background of this activity stems from the limited diversification of coffee products, since most farmers only market ground or roasted beans, resulting in low economic value. To address this issue, the program introduced an alternative approach that preserved the identity of coffee while opening new economic opportunities. The method was carried out through a workshop with local PKK women, which consisted of socialization on the importance of product diversification, hands-on practice in making coffee noodles (dough preparation, molding, boiling, and serving), and discussion on marketing strategies suitable for small businesses. The results indicated an increase in participants’ skills and knowledge in processing coffee into an innovative food product with a chewy texture, distinctive aroma, and unique taste that received positive feedback. Beyond producing a new product, the program also encouraged entrepreneurial awareness, strengthened collaboration, and motivated the establishment of small business groups oriented toward local economic development. Therefore, coffee noodle innovation has the potential to become a signature village product in Sagalaherang village while supporting empowerment and strengthening community economic independence